Advanced Technology in Teaching - Proceedings of the 2009 3rd International Conference on Teaching and Computational Science (WTCS 2009) Volume 1: Intelligent Ubiquitous Computing and Education - Wu, Yanwen (Advances in Intelligent and Soft Computing,, 2012)
The volume includes a set of selected papers extended and revised from the International Conference on Teaching and Computational Science (WTCS 2009) held on December 19- 20, 2009, Shenzhen, China.   WTCS 2009 best papers Volume 1 is to provide a forum for researchers, educators, engineers, and government officials involved in the general areas of Intelligent Ubiquitous Computing and Education to disseminate their latest research results and exchange views on the future research directions of these fields. 128 high-quality papers are included in the volume. Each paper has been peer-reviewed by at least 2 program committee members and selected by the volume editor Prof.Wu.   On behalf of the WTCS 2009, we would like to express our sincere appreciation to all of authors and referees for their efforts reviewing the papers. Hoping you can find lots of profound research ideas and results on the related fields of Intelligent Ubiquitous Computing and Education.